The Technological Advance and Application of Coprolite Analysis - Yang, Liu; Zhang, Xing; Zhao, Xingbo; Xiang, Hai (Frontiers in Ecology and Evolution, 2022)
Coprolites (mummified or fossilized faeces), belonging to the group of ichnofossils, are fossilised remains of faeces produced by animals. Various types of data from coprolites provide detailed evidence of the producer`s condition, like diet, intestinal microbiome, virus infection and parasites diseases. In addition, the palaeoenvironment information relevant to producers` ecological niche can be drawn from taphonomy details the coprolites mirrored. At present, the phylogenetic clues of the producer`s population can be determined by advanced molecular biotechnologies. With the integration of multiple methods and techniques, coprolite has been widely accepted as an ideal material to study the diet, evolution, and palaeoenvironment of producers. In this paper, we reviewed the history of coprolite research, enumerated and interpreted the data recovered from coprolites, and explained their research value to palaeocoprology and evolutionary biology. Finally, we summarized the current directions of coprolite research and looked into its future prospects.